Parametrized formulations of Hamilton's law for numerical solutions of dynamic problems: Part II. Time finite element approximation - Sheng, G.; Fung, T. C.; Fan, S. C. (Computational mechanics, 1998)
In part I of this paper, we presented a consistent mathematical perspective to the formulations of Hamilton's law and unified the formulations by parametrized form with global approximation. In part II of this paper, we extend the formulations to a proper form to develop high-performance time finite elements for numerical solutions of dynamic problems. The two-field mixed formulations are emphasized and the particular features of using lower order interpolation functions are discussed.